implementasi Hukum Anti Monopoli Dan Persaingan tidak sehat Sebagai Sumbangsih Dalam Pembangunan Di Indonesia - Azwar Pakaya (Universitas Negeri Gorontalo, 2009)
Economics crisis affecting at crisis in all areas, started from practice of indisposed economic activity. Competition faced by economic perpetrator in 21th century is competition in global area. In order to growing and extends economics concept that prohibiting of practices of indisposed monopolies and emulation to all national entrepreneur intplemented as according to nationality economics theme, its will be face to faces with various challenges and constraint. The Consraint or challenge is inter alia, in the form: Firstly, continuously corruption, collution and nepotism (KKN). Second, collection bureaucracy. Third, dependency at credit. Fourth, overseas debt. Fifth international and domestic market. With implementaion of UU No. 5/1999 about Prohibition Of Monopoly Practices and Emulation of lndisposed Business and UU No 8/1999 about Consumerism, hence pushing the business perpetrator fo trying corupetitively in corporate world and consumer will not sacrificed. Kata Kunci: Hukum, Anti Monopoli, Persaingan Tidak Sehat, Pembangunan.